interview, Ghada Amer, French, - Fuencisla Zomeño (Studies in 20th & 21st Century Literature, 2002)
This paper analyzes the influence of postmodernism in Paloma Díaz-Mas's feminist approach through two short stories, "The World According to Valdés," and "In Search of a Portrait." The political situation after Franco's death embraced democracy which allowed writers to pay more attention to intellectual concerns. Women writers steered the radical positions of the 1970s toward a more philosophical and intellectual analysis of reality and artistic expression during the eighties. In these two short stories, Díaz-Mas addresses women's issues by questioning the scope of modernist and humanist views. She criticizes the modernist concept of unity (text/identity) pointing out the discrimination that this unity creates in art, through the distinction between high art/mass culture; and in the individual, through the distinction between feminine/masculine and high/low. Even though Díaz-Mas's main characters in the two stories are women, she does not solely focus on defending them, but she contrasts present and past to parody the causes which produce discrimination in the social and artistic processes.
Keywords: feminism; postmodernism; Paloma Díaz-Mas; feminist approach; the World According to Valdés; In Search of a Portrait; Franco; philosophy; intellectualism; modernist view; humanist view; high art/mass culture